Games go abroad. - (:unkn) unknown (My University, 2006)
The research that is reported in this paper is part of an on going collaboration between two universities and two schools on two continents. It began in 2001 as a small scale literacy study: Critical literacy, social action and children’s representations of ‘place’. Fun and games is a book produced by Grade 4 children at Phepo school, a poor school in Atteridgeville, an African township outside of Pretoria for students at Ridley Grove, a poor school in Adelaide, South Australia. The challenge for the teacher was to support young children who speak different African languages and who are learning through the medium of Setswana to show and explain their games to children in an English medium school, living in Australia. Multiple forms of semiosis - words, drawings, photographs, models, video - were essential resources for meeting this challenge as was the use of children's multilingual repertoires for the production of an English text. This classroom project on children's games is theorised in relation to the use of out-of-school literacies in education, multilingualism as a pedagogic resource and multimodal literacies. The extent to which this work on games contributes to the overarching critical literacy project is considered with reference to the interlocking dimensions of power, diversity, access and design, enlivened by children's pleasure when the worlds that they enjoy are embraced by their schools.
Keywords: Critical literacy; Semiosis; Multilingualism; Multimodal literacies